ANALISIS STRUKTUR DAN SIFAT MAGNETIC PEROVSKITE LaMnO3 SEBAGAI KANDIDAT BAHAN ABSORBER GELOMBANG ELEKTROMAGNETIK[Effect of Structure Analysis and Magnetic Properties of Perovskite LaMnO3 as for Candidate Materials Absorber Electromagnetic Wave.] - Sebleku, Pius; Adi, Wisnu Ari (Jurnal Metalurgi, 2013)
The synthesis and characterization of LaMnO3 magnetic materials by mechanical alloying process have been performed. This magnetic material is prepared by oxides, namely La2O3, and MnCO3. The mixture was milled for 10 h then sintered at a temperature of 1000 ° C for 10 h. The refinement results of x-ray diffraction pattern of lanthanum manganite showed that the sample had single phases, namely, LaMnO3 phases. LaMnO3 phase had a monoclinic structure (I12/a1) a = 5.4638(7) Å, b = 5.5116(6) Å and c = 7.768(1) Å,  = 90°and  = 90.786(9) 0°, the unit cell volume of V = 233.93(3) Å3, and the atomic density of  = 6.449 gr.cm-3. The results of elementary analysis and particle morphology appears that the sample has a composition as expected with a relatively uniform particle shape and evenly distributed the surface of the sample. The electromagnetic wave absorption phenomenon has occurred in the frequency range of 9-15 GHz with absorption of ~ 2.6 dB at 11 GHz peak frequency. The electromagnetic wave absorption is calculated about 30 % with a thickness of 1.5 mm. We concluded that the material lanthanum manganite perovskite system LaMnO3 can be used as a preliminary study of the development of new materials for electromagnetic wave absorber.